Diseño de estrategias de enseñanza del inglés y estilos de aprendizaje. Un estudio basado en los estudiantes de la Institución Educativa Olga González Arraut de la ciudad de Cartagena. (2017)
This document shows the results of a descriptive research that seeks to design English teaching strategies based on the learning styles from fourth and fifth grade students at Olga González Arraut School in Cartagena de Indias. This project was designed taking into account the shortcomings found in the English teaching strategies used by the teachers who are not truly English teachers. Fourth and fifth grade students were chosen to be applied a survey in the first school period in 2017 year. The students who were given a survey to determine their preferences and learning styles were randomly chosen. Besides, classroom observations and analysis of students were made. They were analyzed to describe the strategies used by teachers, and student attitude. The Likert scale was applied to English teachers. At the end, these results led to the design of a variety of strategies and techniques in accordance with the proposals